Proses Demokrasi melalui Pilkada yang Berkualitas menuju Pemimpin Bali - Dewa Putu Mantera (Badan Riset dan Inovasi Daerah Provinsi Bali, 2018)
The general elections to choose regional leaders in the province of Bali is mandated by Undang-undang Nomor 10 Tahun 2016 tentang Pilkada (Law Number 10 Year 2016 about local leader election). Pilkada (pemilihan kepala daerah) or the local leader election based on the principle of democracy, they are “direct, general, free and secret, honest, and fair (langsung, umum, bebas dan rahasia, jujur dan adil or luberjurdil)” based on Pancasila and the 1945 constitution. Pilkada is the responsibility of the central government and local government so that the community can actively exercise their suffrage and obtain comprehensive information on the stages, profiles or figures, and capacity of Paslon (pasangan calon, the candidates). Selection of regional heads simultaneously in 2018 in the Province of Bali has been running safely, orderly, and successful so it is expected to produce a good Bali leader. This year the election is to choose the Governor and Vice Governor of Bali, the Bupati and Wakil Bupati (the head and vice head of the regency) in Gianyar Regency and Klungkung Regency.